2014
DOI: 10.1002/clen.201300632
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fluoride from Aqueous Solution Using Aluminum Alginate Beads

Abstract: Fluoride is a contaminant in groundwater; hence numerous procedures for its removal are reported. Adsorption studies are specified as effective methods for removal of fluoride contamination from water sources. In the present study, aluminum crosslinked alginate beads are used as an adsorbent for fluoride removal from aqueous solutions. Adsorption experiments were carried out by batch contact method. The equilibrium was achieved in 4 h. Optimal conditions were found to be pH 2 at 25°C, giving rise to 99.5% remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…the Ho-McKay model, the second-order rate and the Roginsky-Zeldovich-Elovich equation, Eqs. (S12)-(S18), respectively, applying both linear and nonlinear least-squares methods (Kaygusuz et al 2015). The best correlation was obtained using non-linear fitting with PSO equation (Table S11).…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…the Ho-McKay model, the second-order rate and the Roginsky-Zeldovich-Elovich equation, Eqs. (S12)-(S18), respectively, applying both linear and nonlinear least-squares methods (Kaygusuz et al 2015). The best correlation was obtained using non-linear fitting with PSO equation (Table S11).…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Alginate solution (4% w/v) was mixed with a rhamanolipid solution (0.1% w/v) at 80 • C for 2 h, and then a copper standards solution was put into the mixture (Figure 1) [24][25][26][27]. A small amount of copper standard solution, 5 mL of 100 mg/L, was adopted for this preliminary study.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A number of studies were reported for the removal of fluoride using chitosan biopolymer based sorbents, lanthanum entrapped chitosan composite [5], zirconium encapsulated chitosan matrix [6], lanthanum-zirconium chitosan composite [7], hydrous ferric oxide doped alginate beads [8], Fe(III)-Zr(IV) binary oxide loaded calcium alginate beads [9], aluminium loaded alginate beads [10], metal loaded carboxylated alginate acid [11] etc. Similarly, aluminium and lanthanum modified adsorbents showed higher defluoridation capacity due to their high selectivity and chemical affinity towards fluoride than the respective bare alumina and lanthanum.…”
Section: Introductionmentioning
confidence: 99%